Representasi Nilai Sosial, Ekonomi, dan Pendidikan dalam Novel Bekisar Merah Karya Ahmad Tohari : Analisis Sosiologi Sastra - Aqrima Imaroh; Fiki Nushrotul Hafidh; Jihan Aina Nabila (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This research looks at the problem of what social, economic, and educational aspects are contained in the novel “Bekisar Merah” by Ahmad Tohari. The purpose of this research is to obtain the results of the analysis of the novel using the sociology of literature approach. This type of research is descriptive qualitative research and the data used in conducting this research are sentences and dialogues that show social aspects, economic aspects, and educational aspects in the novel “Bekisar Merah” by Ahmad Tohari. The data collection techniques used in this research are reading and note-taking techniques. The results of this research are social aspects, economic aspects and educational aspects contained in the novel “Bekisar Merah” by Ahmad Tohari.